Healing-promoting effect of bombesin treatment on chronic gastric ulcer in rats - (:unkn) unknown (ELSEVIER SCIENCE BV, 2002)
To evaluate whether bombesin treatment has a facilitatory effect on the healing of chronic gastric ulcer, following the induction of ulcer by serosal application of acetic acid, rats were given bombesin (30 mug/kg/day; subcutaneously) or vehicle three times a day for 7, 14 or 21 days until they were decapitated. Neither food intake nor gastric emptying rate in either vehicle-treated or bombesin-treated groups was not statistically different from control rats. Similarly, ulcer indices and gastric myeloperoxidase (MPO) activities at the first and second weeks of injury were not different among the groups. However, in the 3-week ulcer group, bombesin treatment reduced tissue MPO level significantly back to control levels. Moreover, the analysis of the surface epithelium by scanning electron and light microscopy demonstrated a significant reduction in the severity of ulcers by bombesin treatment. Pretreatment with CCK antagonists (L-364,718 or L365,260; 25 mumol/kg/day) before bombesin treatment showed that neither of the CCK antagonists had a significant effect on the bombes in-mediated healing process, suggesting that CCK receptors are not involved in the action of bombesin. In accordance with the previous studies that show its acute gastroprotective effects, bombesin is also effective in promoting the healing process of chronic gastric ulcer in rats. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: acetic acid; gastrin-releasing peptide; ulcer index; myeloperoxidase; scanning electron microscopy; MUCOSAL GROWTH; SOMATOSTATIN; RECEPTORS; PEPTIDE; INJURY